Quantitative model for predicting the desorption energy of water contained in lignite. (1st October 2015) - Huang, Qunxing; Zhou, Guoshun; Yu, Ben; Wang, Shoukang; Chi, Yong; Yan, Jianhua
Abstract: Due to the high moisture content (25–65%) dewatering is essential for the clean and efficient utilization of lignite as fuel or feedstock for chemical industry. In order to quantitatively evaluate the desorption energy of contained water content, a prediction model was proposed in this paper based on Lennard-Jones 10-4-3 solid–fluid potential equation and Clausius–Clapeyron principle using lignite pore structure and specific surface area. Based on the proposed model, the drying behavior of two typical Chinese lignite respectively collected from coal mine at Xinjiang and Inner Mongolia districts were experimentally studied and intelligent gravimetric analysis (IGA) was employed for model evaluation. Results show that the water content of original coal sample are 22.4% and 37.6% by weight for Xinjiang and Inner Mongolia lignite, respectively. After air drying at 40 °C, the water content can be dramatically reduced to 13.4% and 17.9%. The overall dewatering energy of the retained moisture after air dying are 38.84 kJ/(100 g air dried coal) for Xinjiang lignite and 53.57 kJ/(100 g air dried coal) for Inner Mongolia lignite. From IGA analysis, it was found that the gradient of the desorption energy of Xinjiang lignite against water content can be separated into three main water desorption stages according to the energy cost.